Fenomena Jual Beli Username Twitter sebagai Ajang Eksistensi Diri (Studi Fenomenologi Konstruksi Identitas Roleplayer) - Winarty, Shenthya; Puspita, Ratna (Magister of Communication Science, Sahid University Jakarta., 2023)
Roleplay is a game played on social media where individuals assume the persona of an artist and manage corresponding social media accounts. This activity involves building a social media identity, with many roleplayers attempting to do so optimally, even resorting to buying usernames at relatively high prices for survival. This research adopts a phenomenological approach, employing observational data collection techniques, and participant interviews, and explores the process of buying and selling usernames on Twitter.The results of this study reveal two primary methods for username transactions: manual searching through the platform's search bar using specific keywords and utilizing Autobase, a tool designed explicitly for buying and selling purposes. Beyond detailing the procedural aspects of username transactions, the research delves into the motives driving individuals to engage in roleplay. One enduring method in roleplaying is the acquisition of usernames, motivated by identity consistency and personal enjoyment. However, the significance of being a roleplayer extends beyond username acquisition. This study emphasizes that the existence of roleplayers is not solely measured by the quality of their usernames. Participants acknowledge that cultivating a positive character and image is equally crucial for their continued presence in the roleplay community.